2011
DOI: 10.1007/s10295-011-1020-x
|View full text |Cite
|
Sign up to set email alerts
|

Detection and identification of microorganisms in wine: a review of molecular techniques

Abstract: The microbial ecology of wine is complex. Microbes can play both positive and negative roles in the quality of the final product. Due to this impact, the microbial ecology of wine has been well studied. Traditional indirect methods, such as plating, have largely been replaced by a number of molecular methods. These methods are typically either indirect methods used for identification of cultured organisms, or direct methods used to profile whole populations or identify specific microbes in a mixed population. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 113 publications
(166 reference statements)
0
16
0
1
Order By: Relevance
“…plantarum in traditional wines. In detail, if PCR-DGGE analysis and 16S rRNA gene sequencing can be considered by now suitable tools to identify lactobacilli from wines (Bokulich et al 2012; Ivey and Phister 2011), RAPD-PCR technique revealed an unexpected biodiversity among Lb. plantarum strains isolated from different wines.…”
Section: Discussionmentioning
confidence: 99%
“…plantarum in traditional wines. In detail, if PCR-DGGE analysis and 16S rRNA gene sequencing can be considered by now suitable tools to identify lactobacilli from wines (Bokulich et al 2012; Ivey and Phister 2011), RAPD-PCR technique revealed an unexpected biodiversity among Lb. plantarum strains isolated from different wines.…”
Section: Discussionmentioning
confidence: 99%
“…This technique has been developed to detect and quantify total yeasts (Hierro et al, 2006a), Brettanomyces (Phister and Mills, 2003; Delaherche et al, 2004; Tofalo et al, 2012; Willenburg and Divol, 2012; Vendrame et al, 2014), Hanseniaspora (Hierro et al, 2007; Phister et al, 2007), Saccharomyces (Martorell et al, 2005b; Hierro et al, 2007; Salinas et al, 2009), and Zygosaccharomyces (Rawsthorne and Phister, 2006) in wine and other fermentation processes. The main disadvantage other than cost and personnel training lies in the method’s inability to differentiate viable and non-viable microbes (Ivey and Phister, 2011). Several possible solutions have been indicated to overcome the detection of non-viable microorganisms; e.g., using RNA as a target for PCR amplification (Bleve et al, 2003; Hierro et al, 2006a) because, in theory, RNA is much more unstable than DNA, and is considered an indicator of viability; or using a fluorescent photoaffinity label which covalently couples to nucleic acids upon exposure to light, such as EMA and PMA (Andorrà et al, 2010).…”
Section: Methods To Detect Genetic Polymorphismmentioning
confidence: 99%
“…Fingerprinting generally examines the whole genome of an organism by often creating a banding pattern by digesting or amplifying genome regions that can be compared between organisms (Ivey and Phister, 2011). Fingerprinting methods are characterized because they present a sufficient degree of genetic polymorphism to differentiate between strains of the same yeast species.…”
Section: Methods To Detect Genetic Polymorphismmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to the development of this method, the sole detection of live cells was accomplished by using reverse transcription (RT) to obtain cDNA, which was sequenced and subsequently quantified using qPCR. The use of this method was time consuming and was prone to error due to the many steps involved, the low stability of RNA under harsh conditions (Ivey and Phister, 2011), and the high variability in RNA transcription (Vendrame et al, 2014). The PMA method has been optimized for qPCR with respect to temperature, PMA concentration, and time of incubation (Andorra et al 2010;Nkuipou-Kenfack et al, 2013).…”
Section: Introductionmentioning
confidence: 99%